Evidence-Based Medicine in the Field of Ophthalmology during the COVID-19 Pandemic - Eyal Walter; Brice Vofo; Alan Jotkowitz; Jaime Levy (Journal of Ophthalmology)
Purpose. To describe the evolution of COVID-19 related publications in the field of ophthalmology. Methods. All articles published in the field of ophthalmology and relevant to COVID-19 were identified by conducting a search on PubMed and Scopus databases using the string ((ophthalmology) OR (eye) OR (ocular)) AND ((corona) OR (COVID-19) OR (pandemic)). Search was conducted on September 30, 2020. Each eligible publication was independently graded by two experienced ophthalmologists based on the level of evidence-based medicine (EBM), with scores ranging from 1 (the highest level of EBM) to 5 (the lowest level). The average level of EBM was also evaluated for each month from February through September. Finally, we analyzed the interval (in days) between submission and acceptance for publication as well as the percentage of manuscripts that required revision before being accepted. Results. Our search yielded a total of 425 relevant publications. Of these publications, 359 (84.5%), 59 (13.9%), and 7 (1.6%) were rated as level 5, 4, and 3, respectively; none of the publications was rated as level 1 or 2. From February 2020 through September 2020, we found a significant increase in the relative proportion of level 3 and 4 publications compared to level 5 publications (rho = 0.108, p=0.024). Moreover, the number of citations per article was significantly correlated with the level of EBM (rho = 2.44, p<0.0005); however, we found no correlation between the number of citations and either the month of publication or the ranking of the journal in which the article was published. The mean interval between submission and acceptance for publication was 20.4 days (SD: 20.2 days), and 48.2% of submitted manuscripts were accepted without revision. From February through September, the interval between submission and acceptance increased significantly (rho = 0.515, p<0.0005); however, we found no significant change in the percentage of publications that were accepted without revision over this same time period. Conclusions. In the early months of the COVID-19 pandemic, primarily lower-level EBM articles were published, and these publications were accepted relatively quickly. However, this effect was temporary, and over time the EBM levels improved and the interval between submission and acceptance increased, indicating an increase in publication standards.